Structural Variation of Chondroitin Sulfate Chains Contributes to the Molecular Heterogeneity of Perineuronal Nets - Miyata, Shinji; Nadanaka, Satomi; Igarashi, Michihiro; Kitagawa, Hiroshi (Frontiers in Integrative Neuroscience, 2018)
Aggrecan, a chondroitin sulfate proteoglycan, forms lattice-like extracellular matrix structures called perineuronal nets (PNNs). Neocortical PNNs primarily ensheath parvalbumin-expressing inhibitory neurons (PV cells) late in brain development. Emerging evidence indicates that PNNs promote the maturation of PV cells by enhancing the incorporation of homeobox protein Otx2 and regulating experience-dependent neural plasticity. Wisteria floribunda agglutinin (WFA), an N-acetylgalactosamine-specific plant lectin, binds to the chondroitin sulfate (CS) chains of aggrecan and has been widely used to visualize PNNs. Although PNNs show substantial molecular heterogeneity, the importance of this heterogeneity in neural plasticity remains unknown. Here, in addition to WFA lectin, we used the two monoclonal antibodies Cat315 and Cat316, both of which recognize the glycan structures of aggrecan, to investigate the molecular heterogeneity of PNNs. WFA detected the highest number of PNNs in all cortical layers, whereas Cat315 and Cat316 labeled only a subset of PNNs. WFA+, Cat315+, and Cat316+ PNNs showed different laminar distributions in the adult visual cortex. WFA, Cat315, and Cat316 detected distinct, but partially overlapping, populations of PNNs. Based on the reactivities of these probes, we categorized PNNs into four groups. We found that two subpopulation of PNNs, one with higher and one with lower WFA-staining are differentially labeled by Cat316 and Cat315, respectively. CS chains recognized by Cat316 were diminished in mice deficient in an enzyme involved in the initiation of CS-biosynthesis. Furthermore, WFA+ and Cat316+ aggrecan were spatially segregated and formed microdomains in a single PNN. Otx2 co-localized with Cat316+ but not with WFA+ aggrecan in PNNs. Our results suggest that the heterogeneity of PNNs around PV cells may affect the functional maturation of these cells.